Examining the factor structures of the five facet mindfulness questionnaire and the self-compassion scale. - Williams, M; Dalgleish, T; Karl, A; Kuyken, W (American Psychological Association Inc., 2014)
The five facet mindfulness questionnaire (FFMQ; Baer, Smith, Hopkins, Krietemeyer, and Toney, 2006) and the self-compassion scale (SCS; Neff, 2003) are widely used measures of mindfulness and self-compassion in mindfulness-based intervention research. The psychometric properties of the FFMQ and the SCS need to be independently replicated in community samples and relevant clinical samples to support their use. Our primary aim was to establish the factor structures of the FFMQ and SCS in individuals with recurrent depression in remission, since mindfulness-based cognitive therapy (MBCT) was developed as a treatment for preventing depressive relapse. In order to determine the consistency across populations, we examined the factor structures of the FFMQ and SCS in 3 samples: (1) a convenience sample of adults, (2) a sample of adults who practice meditation, and (3) a sample of adults who suffer from recurrent depression and were recruited to take part in a trial of MBCT. Confirmatory factor analyses (CFAs) showed that a 4-factor hierarchical model of the FFMQ best fits the community sample and the clinical sample but that a 5-factor hierarchical model of the FFMQ best fits the meditator sample. CFA did not endorse the SCS 6-factor hierarchical structure in any of the 3 samples. Clinicians and researchers should be aware of the psychometric properties of the FFMQ to measure mindfulness when comparing meditators and nonmeditators. Further research is needed to develop a more psychometrically robust measure of self-compassion.